Few-layer 1T′ MoTe2 as gapless semimetal with thickness dependent carrier transport. (12th June 2018) - Song, Peng; Hsu, Chuanghan; Zhao, Meng; Zhao, Xiaoxu; Chang, Tay-Rong; Teng, Jinghua; Lin, Hsin; Loh, Kian Ping
Abstract: Semimetal MoTe2 can be a type II Weyl semimetal in the bulk, but monolayer of this material is predicted to be quantum spin hall insulators. This dramatic change in electronic properties with number of layers is an excellent example of the dimensional effects of quantum transport. However, a detailed experimental study of the carrier transport and band structure of ultrathin semimetal MoTe2 is lacking so far. We performed magneto-transport measurements to study the conduction behavior and quantum phase coherence of 1T′ MoTe2 as a function of its thickness. We show that due to a unique two-band transport mechanism (synergetic contribution from electron conduction and hole conduction), the conduction behavior of 1T′ MoTe2 changes from metallic to p-type unipolar, and finally to ambipolar as the thickness decreases, suggesting that this effect can be used in devices by effectively controlling the thickness. Our transport studies, optical measurements and first-principles electronic structure calculations reveal that 1T′ MoTe2 remains gapless down to a few ( 2–3) layers. Despite being gapless, 1T′ MoTe2 exhibits metal-insulator transition at 3-layer thickness, due to enhanced carrier localization effect.